Properties of Magnetohydrodynamic normal modes in the Earth's magnetosphere - Hartinger,MD; Elsden,T; Archer,MO; Takahashi,K; Wright,AN; Artemyev,A; Zhang,X; Angelopoulos,V (JGR: Space Physics, 2023)
The Earth's magnetosphere supports a variety of Magnetohydrodynamic (MHD) normal modes with Ultra Low Frequencies (ULF) including standing Alfvén waves and cavity/waveguide modes. Their amplitudes and frequencies depend in part on the properties of the magnetosphere (size of cavity, wave speed distribution). In this work, we use ∼13 years of Time History of Events and Macroscale Interactions during Substorms satellite magnetic field observations, combined with linearized MHD numerical simulations, to examine the properties of MHD normal modes in the region L > 5 and for frequencies <80 mHz. We identify persistent normal mode structure in observed dawn sector power spectra with frequency-dependent wave power peaks like those obtained from simulation ensemble averages, where the simulations assume different radial Alfvén speed profiles and magnetopause locations. We further show with both observations and simulations how frequency-dependent wave power peaks at L > 5 depend on both the magnetopause location and the location of peaks in the radial Alfvén speed profile. Finally, we discuss how these results might be used to better model radiation belt electron dynamics related to ULF waves.